Pengaruh Model Pembelajaran Mind Mapping terhadap Hasil Belajar Matematika Siswa - Anastasia Marxy (Universitas Indraprasta PGRI, 2017)
The Impacts of Mind Mapping Learning Method on Student’s Mathematics Achievement. The purpose of this research is to determine The Impacts of Mind Mapping Learning Method on Student’s Mathematics Achievement at SMP Yasdiqin Citeurup raya street Bekasi, Rt 02 Rw 05 empirically. The method used in the research is experiment, sampling technique is random sampling. The instrument for data collection is multiple choice test consist of 25 items and the data was validated empirically. Data analysis technique is t test, and based on t test, t test is 3.15 and t table is 1.70 at significance level of 5 %. It means t test ? t table (3.15 ? 1.70), it can be concluded that the average of student’s Mathematics achievement through mind mapping learning method is more than cooperative learning type STAD on student’s mathematics achievement.